Spoken language and attitudes in Hong Kong: English leads in prestige, mandarin rises in employability, and Cantonese faces challenges - Lap Man Cheung; Xiangbin Teng (PLoS ONE, 2026)
Language serves not only as a means of communication but also carries cultural, historical, and socio-economic implications associated with its speakers. These associations can reflect social dynamics and attitudes towards different groups within a society, influencing important decisions in areas such as employment and government. This study employed a modified matched-guise test to investigate how a person’s perceived traits are influenced by the language they speak—Cantonese, English, or Mandarin—in Hong Kong, a multilingual city with a unique Cantonese culture, a history as a British colony, and now a special administrative region of China. In an online questionnaire, 541 participants listened to recordings of the same group of speakers in one of the three languages and rated the speakers on attributes such as competence, prestige, and employability. The findings revealed that speaking English was rated highest in intelligence and prestige, while Mandarin speakers were favored in employability and goodwill. Cantonese was comparable to Mandarin but did not show any favored association. These results suggest that implicit group categorizations associated with certain languages are attributed to those speaking the language, contributing to our understanding of language-based social judgments. This study underscores the need for awareness of the influence of these stereotypical associations in various professional and societal scenarios in multilingual societies such as Hong Kong.